2018
DOI: 10.2136/sssaj2017.12.0417
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Additions Promote Decomposition of Soil Organic Carbon in a Tibetan Alpine Meadow

Abstract: Core Ideas Litter addition increased C decomposition. Litter properties were more important than abiotic soil properties in controlling C decomposition. N addition would increase decomposition of SOC with added litter and decrease SOC accumulation by altering litter quality. In grassland ecosystems, nitrogen (N)‐induced changes in plant community often affect grassland soil organic carbon (SOC) decomposition and accumulation. However, there is no consensus on the biological and chemical mechanisms that underli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…This finding is in agreement with our results. On the other hand, N addition has been found to reduce the SOC content and increase the decomposition of SOC vis changes in belowground chemical properties and aboveground plants in a Tibetan alpine meadow [18]. The SOC concentration in the 0-10 cm soil layer showed no response to N addition in a semiarid grassland [19].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This finding is in agreement with our results. On the other hand, N addition has been found to reduce the SOC content and increase the decomposition of SOC vis changes in belowground chemical properties and aboveground plants in a Tibetan alpine meadow [18]. The SOC concentration in the 0-10 cm soil layer showed no response to N addition in a semiarid grassland [19].…”
Section: Discussionmentioning
confidence: 93%
“…The critical N load is estimated to be between 8 and 10 g N m −2 year −1 [16]. Conversely, the SOC content was reduced following N addition in a Pinus tabuliformis forest [17] and Tibetan alpine meadow [18], especially in the 10-20 cm soil layer [19]. Research has found that N addition tends to enhance SOC mineralization [20].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient supply, especially nitrogen (N) and phosphorus (P) availability, strongly affects C cycling and storage in grasslands ecosystems (Li et al, 2018; Luo et al, 2020; Ramirez, Craine, & Fierer, 2010; Riggs & Hobbie, 2016). N and P additions increase the aboveground plant biomass (Borer, Grace, Harpole, MacDougall, & Seabloom, 2017; Isbell et al, 2013; Li et al, 2014), and increase or decrease biomass allocation to roots (Fornara & Tilman, 2012; Li, Li, et al, 2018). These modifications in plant biomass would, in turn, affect C input to soil and SOC dynamics, however, the effects of N and P additions on SOC decomposition and soil C sequestration had no apparent interrelationship???…”
Section: Introductionmentioning
confidence: 99%
“…N and P additions accelerated SOM decomposition and reduced SOC content in the topsoil of alpine meadows on the Tibetan Plateau (Li et al, 2018; Luo et al, 2019, 2020). The litter quality and various biomass allocations to aboveground plant and roots in different grassland ecosystems may result in varying soil C sequestration and SOC storage due to N and P additions (Fornara & Tilman, 2012; Li, Li, et al, 2018; Soudzilovskaia et al, 2007). Besides these reasons, the inconsistent effects might be due to the differential response of the various microbial compositions (Leff et al, 2015; Riggs & Hobbie, 2016; Zhang, Chen, & Ruan, 2018), and thereby SOM decomposition and accumulation (Chen et al, 2014; Leff et al, 2015; Li, Hou, et al, 2018; Riggs, Hobbie, Bach, Hofmockel, & Kazanski, 2015) to N and P additions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation